Exploratory analysis of predictors of patient adherence to subcutaneous interferon beta-1a in multiple sclerosis: TRACER study. (2nd June 2016) - Paolicelli, Damiano; Cocco, Eleonora; Di Lecce, Valentina; Direnzo, Vita; Moiola, Lucia; Lanzillo, Roberta; Perini, Paola; Malucchi, Simona; Borriello, Giovanna; Portaccio, Emilio; Panetta, Valentina; Fenu, Giuseppe; et al.
ABSTRACT: Objective: The TRACER multicenter retrospective study aimed to collect data on treatment adherence in a real-life setting, in order to identify predictors of adherence at baseline. Methods: We recruited 384 relapsing-remitting (RR) multiple sclerosis patients with at least 12 months of use of RebiSmart®. This electronic device records the performed injections and assesses adherence as the percentage of 'not missing doses', through the connection to the iMed database. Subjects with at least 80% of completed doses at the 12 month of therapy were defined 'treatment adherents'. Results: After 12 months, 89.3% of patients were adherent; 93.2% of patients aged 26–40 years at baseline were adherent (vs 79% of the ≤25 and 87.5% of the ≥41 year olds; p = 0.006). Furthermore, 90.5% of patients with a baseline Expanded Disability Status Scale (EDSS) score <4 showed ≥80% adherence (vs 71.4% in those with EDSS score ≥4; p = 0.016). Fifty-four percent of the patients who were not adherent after 3 months were also not adherent after 12 months (OR 16.8; CI 95%:7.1–39.8). Conclusions: Patients aged 26–40 years and with an EDSS score <4 at baseline were the most adherent. The status of 'treatment adherent' in the first 3 months was predictive of higher adherence in the long term.